Rice husk waste characterization: Absorption and absorbance properties for potential renewable energy applications - Zulpadrianto, Zulpadrianto; Yeni Etma Nazar; Faisal Hariman Lubis; Nur Aisyah Ali (Edulab : Majalah Ilmiah Laboratorium Pendidikan, 2025)
Purpose – This study aims to characterize rice husks as a renewable energy source. It measures the absorption and absorbance of rice husk waste. It determines the factors that affect the efficiency of rice husks (RHS) as a renewable energy source. Design/methods/approach – Laboratory experiments and literature reviews were the methods used in this study. Material characterization was performed using a Vector Network Analyzer (VNA) to measure electromagnetic wave absorption and a UV-VIS spectrometer to measure UV absorption. Findings – The results of the VNA measurement of RHS HCl 0M carbon = -3.80 dB; 1M = -13.28dB, and 3M = -12.28 dB. Absorbance measurements were then performed using UV-Vis. Based on the measurements performed, the absorbance values of each material were as follows: RH HCl 0M = 0.187 AU; 1M = 0.084 AU; 3M = 0.141 AU. Research implications/limitations – Exploring the potential of rice husks as an environmentally friendly and sustainable renewable energy source. Analyzing the physical and chemical characteristics of rice husks, including their carbon content, to determine the energy efficiency that can be generated through various conversion technologies such as combustion, activation, and measurement. Originality/value – This study focuses on the potential of rice husks as a renewable energy source.